USING MATLAB TO DETERMINE THE TRAFFIC LIGHT SIGNAL IN A SERIES OF IMAGES - D. Sukharev (Теория и практика судебной экспертизы, 2015)
The method of determining the traffic light on a series of images using MATLAB is proposed and justified.